The Effect of HDI, Unemployment, and Investment on GRDP and Poverty (Efficient: Indonesian Journal of Development Economics, 2023)
Poverty is a major global development problem that must be continuously addressed so that it can be resolved more quickly. The purpose of this study was to find out direct and indirect effects of HDI, unemployment, and investment variables on GRDP and poverty during the 2017-2020 period. This type of research is quantitative descriptive research and the data used are secondary data. This study used a research method, namely panel data in the 2017-2020 period, with the fixed effect model (FEM) technique as the best technique. The interpretation method used a panel data regression analysis tool from the FEM method and path analysis. The result showed that the variables HDI (X1), Unemployment (X2) and Investment (X3) had a significant effect both directly on poverty (Z) and indirectly through GRDP (Yi) on poverty (Z). Then based on the result of the path analysis, HDI gives the biggest contribution in influencing the poverty level in Central Java Province.